2013 5th International Workshop on Software Engineering in Health Care (SEHC) 2013
DOI: 10.1109/sehc.2013.6602471
|View full text |Cite
|
Sign up to set email alerts
|

An agile V-model for medical device software development to overcome the challenges with plan-driven software development lifecycles

Abstract: Abstract-Through the use of semi structured interviews with medical device software organizations it emerged that medical device software organizations are experiencing difficulties when following plan driven Software Development Life Cycles (SDLC), particularly in the area of requirements management. To attempt to resolve these issues an examination of the non-regulated industry was performed to determine if lessons learned there could be applied to the development of medical device software. This examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…McHugh et al mention that "for agile methods to succeed, an organisation must be structured in a way to accommodate agile methods" [3]. McHugh, Cawley, McCaffery, Richardson and Wang summarize that there is evidence of gaining significant organisational benefits upon the adoption of an agile method for managing and performing software development projects [4]. While there is sufficient of scientific literature on organisational requirements for optimal agile adoption, there is no literature elaborating this knowledge about pharmaceutical companies.…”
Section: Introductionmentioning
confidence: 99%
“…McHugh et al mention that "for agile methods to succeed, an organisation must be structured in a way to accommodate agile methods" [3]. McHugh, Cawley, McCaffery, Richardson and Wang summarize that there is evidence of gaining significant organisational benefits upon the adoption of an agile method for managing and performing software development projects [4]. While there is sufficient of scientific literature on organisational requirements for optimal agile adoption, there is no literature elaborating this knowledge about pharmaceutical companies.…”
Section: Introductionmentioning
confidence: 99%
“…Simply, with the diversification of the software market and the vast ranges of complexity and volatility of the software engineering/development task there can be no one-size-fits-all process model. Practically, this means that organisations and practitioners adopt and adapt models as their needs change (see, for instance, [21], [8]). …”
Section: Introductionmentioning
confidence: 99%
“…As a result, research was conducted into the use of agile approaches in this domain. A comprehensive mapping study [10] was performed to identify where agile practices have been used in regulated domains. This mapping study revealed that despite the widespread adoption of agile methods in non-regulated domains there is still a low rate of adoption among software development organizations in regulated domains.…”
Section: Introductionmentioning
confidence: 99%